Installation art as experience of self, in space and time - Kayser, Christine; Coëllier, Sylvie (Curating and interpreting culture., 2021)
Installation art has modified our relationship to art for over fifty years by soliciting the whole body, demonstrating its sensitivity to space, surroundings, and the living beings with which it is constantly interacting. This book analyses this modification of perception through phenomenological approaches convoking Husserl, Heidegger, Merleau-Ponty, as well as Levinas, Depraz, and the neuroscientist Varela. This theoretical framework is implicit in the various case studies which revisit works that have become classic or emblematic by Carl Andre, Bruce Nauman, Dan Graham; inaugural experiments that remain available only through photographic and written archives by Jean-Michel Sanejouand, Philippe Parreno, as well as the influence of the mode in the realm of music. The book also examines the transference of this Western form to Asia, revealing how it resonates with ancient Asian representations and practices-often associated with the spiritual.The distinct chapters underpin the role of space as a metaframe, the common ground of the various installations. While the nature and agency of space varies-from social, historical space, leisurely or political space, inner psychological space, to shared empty space-these installations reveal the chiasm between the individual body and the outside space. The chapters bear testimony of the process in which the physical journey of the spectator's body within a material-at times invisible-space and its structural components takes place in time, as a succession of micro-experiences.'Installation art as experience of self, in space and time' adds to the existing literature of art history a level of theoretical, experiential and transcultural analysis that will make this inquiry relevant to both university students and independent researchers in the academic fields of philosophy, psychology, aesthetics, art theory and history, religious and Asian studies.